Solitudine, ribellione, rifiuto - Anzilotti, Carlo (Il sogno della farfalla, 2017)
The article speaks of Massimo Fagioli and of his outstanding contribution to our journal and to the education of the psychotherapists who are also the members of its Editorial Committee. The death of Fagioli and the end of the seminars of Analisi collettiva raise several issues as far as the education of future psychotherapists and the future of psychiatric research are concerned. The author gives a few hints for discussion and invites his colleagues to put forth their ideas on these topics, starting from what the seminars of Analisi collettiva represented and from Fagioli’s lifelong human and scientific experiences. In the appendix, the author publishes the letter Fagioli addressed to the Italian Psychoanalytic Society in 1975 to reply to their summons. It represents the first act of a trial which, soon afterwards, ended up in the exclusion of Fagioli from this association. In this letter, Fagioli strongly refuses to having to explain his own activities and behaviour, and asserts his own identity and personal learning and development. The author analyses this assertion by highlighting the dimensions of solitude, rebellion, refusal and freedom which deeply resonate with the behaviour, approach and thinking of Massimo Fagioli.